The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.preteyeres.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Leber congenital amaurosis due to RPE65 mutations and its treatment with gene therapy

Abstract: Leber congenital amaurosis (LCA) is a rare hereditary retinal degeneration caused by mutations in more than a dozen genes. RPE65, one of these mutated genes, is highly expressed in the retinal pigment epithelium where it encodes the retinoid isomerase enzyme essential for the production of chromophore which forms the visual pigment in rod and cone photoreceptors of the retina. Congenital loss of chromophore production due to RPE65-deficiency together with progressive photoreceptor degeneration cause severe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
193
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(199 citation statements)
references
References 199 publications
(548 reference statements)
2
193
0
4
Order By: Relevance
“…In human clinical trials to date, AAV-vectored gene therapy for the RPE65 form of Leber congenital amaurosis (LCA) has shown improvement of some aspects of vision (36,37), but there is recent evidence in patients from two of the ongoing trials that such intervention has not been able to stem the progression rate of retinal degeneration (16,38,39). In naturally occurring canine models, both of RPE65-LCA and others, gene therapy has produced similar results: intervention after the onset of photoreceptor degeneration has not been able to modify the natural history of the disease (16) or to restore visual function unless adjunctive treatments are done (40).…”
Section: Discussionmentioning
confidence: 99%
“…In human clinical trials to date, AAV-vectored gene therapy for the RPE65 form of Leber congenital amaurosis (LCA) has shown improvement of some aspects of vision (36,37), but there is recent evidence in patients from two of the ongoing trials that such intervention has not been able to stem the progression rate of retinal degeneration (16,38,39). In naturally occurring canine models, both of RPE65-LCA and others, gene therapy has produced similar results: intervention after the onset of photoreceptor degeneration has not been able to modify the natural history of the disease (16) or to restore visual function unless adjunctive treatments are done (40).…”
Section: Discussionmentioning
confidence: 99%
“…Breakthrough research has demonstrated visual improvement following gene therapy trials in humans with LCA2. 4,5 Human trials relied on a decade of proof-of-concept studies in canine and rodent models. [6][7][8] Unlike LCA2, in which gene therapy is aimed at correcting an RPE defect, searching for gene therapy for LCA1 will involve an attempt at treating the photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key components of the visual cycle is the retinoid isomerase encoded by the RPEspecific protein 65 kDa (RPE65) gene (2). Mutations in RPE65 cause Leber congenital amaurosis (LCA), a severe childhood blindness (3). RPE65-associated LCA (RPE65-LCA) is a complex disease in which vision loss results from two pathological mechanisms-dysfunction and degeneration of photoreceptors (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Mutations in RPE65 cause Leber congenital amaurosis (LCA), a severe childhood blindness (3). RPE65-associated LCA (RPE65-LCA) is a complex disease in which vision loss results from two pathological mechanisms-dysfunction and degeneration of photoreceptors (3)(4)(5)(6). RPE65-LCA has been proclaimed to be the first successfully treated inherited retinopathy using gene augmentation therapy (7)(8)(9)(10), and the treatment has resulted in substantial improvement in vision that endures at least 3 y (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation